Pengaruh Earning Per Share, Debt to Equity Ratio, dan Current Ratio pada Harga Saham - Wahyu Pranajaya, Kadek; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 25 No 3 (2018), 2018)
Stock price is a very important factor for the capital market players in determining its success, because the rise and fall of stock price will affect the value of a company. This study aims to provide empirical evidence on the influence of Earning Per Share, Debt to Equity Ratio and Current Ratio on Stock Prices. This study was conducted on companies consistently incorporated in the LQ-45 Index during the period 2014-2016. The number of samples taken as many as 29 companiesthe consecutive ones are included in the LQ-45 index, using purposive sampling technique. Data collection was done through non participant observation method with secondary data. The analysis technique used is multiple linear regression analysis.Based on the analysis results found that the variable Earning Per Share and Current Ratio have a positive effect on stock prices while the Debt to Equity Ratio variable has a negative effect on stock prices. Keywords : Earning per share, debt to equity ratio, current ratio, stock price